Nouveaux modes de coordination des acteurs dans le développement local: cas des zones rurales au Bénin - Bernard G. Hounmenou (Développement Durable et Territoires)
The currency development policies in many southern countries, especially in those of sub-Saharan Africa have started a new turn, by the end of the years 1980. With the favor of the democracy climate in many of those countries from that period, number of them have proceeded to the deep reforms, giving to the civil society and the basic populations, an important right of glance in the management of the matters which concern them. One of the important manifestations of those reforms, is expressed by the implementation of the decentralization process. Otherwise, it is also to favor the local populations capacities reinforcement, in order to make them able to well support their own matters management, in the frame of the participative governance, through the decentralization process. Begun in January 1993 with the general statement of territorial administration, the decentralization process in Benin, has known its operational step with the election and the installation of the new local elected, about the beginning of the year 2003. Early, since the middle of the years 1990, in many Benin localities, local communities development experiences have been taking place, in order to prepare populations to the decentralization advent. It’s especially the case of some villages in Atlantic department and all of those in Collines. Through those experiences, various systems of local governance are taking place in rural areas. It’s the case of “village committees of monitoring or management’’, “village committee of development” system in Atlantic region, and the “territory project” system in Collines region. By allowing them to reveal their common preferences of development, the consulting and the mobilization of the local populations inside those systems favor their proximity to the level at which the decisions concerning them are taken.